Morphology of the sacral region and reproductive strategies of Metriorhynchidae : a counter-inductive approach - Herrera, Laura Yanina (2017)
Fil: Herrera, Laura Yanina. División Paleontología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina